Agricultural waste valorisation in Gulf countries: A scoping review toward circular economy and sustainable policy innovation - Nur Fathin, Ruslan; Noormazlinah, Ahmad; Mimi Sakinah, Abdul Munaim; Mohd Zamri, Che Wanik; Sanfilippo, Antonio; Saththasivam, Jayaprakash; Muhammad Qasim, Ali (Springer Nature, 2026)
Agricultural waste presents a critical sustainability challenge across the Gulf Cooperation Council (GCC) countries due to arid climates, limited arable land, and rising food security demands. This scoping review systematically maps existing research on the valorisation of agricultural waste into biofuels, biochar, compost, and adsorbents using the PRISMA-ScR methodology. Searches in Scopus, and Web of Science (until December 2024) identified 354 records. An updated search in October 2025 identified one additional eligible study. After screening, 29 peer-reviewed studies were included for final analysis. By analysing these studies, we identify dominant waste streams (e.g., date palm residues, rice husks), valorisation technologies, and region-specific constraints such as infrastructural gaps, economic viability, and regulatory inertia. The findings demonstrate strong potential for circular economy integration but also reveal policy fragmentation and underexplored economic models in the GCC context. A key limitation is the concentration of studies in Saudi Arabia, which may not fully represent the entire GCC region. We discuss practical implications for low-carbon development and provide future research directions to advance scalable, context-sensitive valorisation pathways. This work contributes to bridging the knowledge-policy gap in agricultural waste reuse and supports broader climate and sustainability transitions in the Gulf region.